/Поmогите пожалуйста\упростите выражения: a. (а-3)(а+3)-2а(4-а) в. (х+5)(х-5)-3х(2-х) д. 3х²(х+4)-(3х-1)(х²-2х+3) е. 2а(а+3b)²-(2a-b)(a²+2b²)

/Поmогите пожалуйста\упростите выражения: a. (а-3)(а+3)-2а(4-а) в. (х+5)(х-5)-3х(2-х) д. 3х²(х+4)-(3х-1)(х²-2х+3) е. 2а(а+3b)²-(2a-b)(a²+2b²)
Гость
Ответ(ы) на вопрос:
Гость
A.(a-3)(a+3)=a^2-3^2=a^2-9 2a(4-a)=8a-2a^2 a^2-9-(8a-2a^2)=a^2-9-8a+2a^2=3a^-8a-9 a^2 -это квадрат B.(x+5)(x-5)=x^2-5^2=x^2-25 3x(2-x)=6x-3x^2 x^2-25-(6x-x^2)=x^2-25-6x+3x^2=5x^2-6x-25 C.3x^2(x+4)=3x^3+12x^2 (3x-1)(x^2-2x+3)=3x^3-6x^2+9x-x^2-2x-3=3x^3-8x^2+7x-3 3x^3+12x^2-(3x^3-8x^2+7x-3)=3x^3+12x^2-3x^3+8x^2-7x+3=20x^2-7x+3
Не нашли ответ?
Ответить на вопрос
Похожие вопросы